Digitalization of the Tax System in Europe - Alina Petraș (Revista de Studii Financiare)
In the context of the highly increasing dispersion of technology in the European economic environment, the interaction of citizens with the public sector is changing rapidly. European countries have significant differences on the tax collection, generating economic effects under a complex fiscal system. The purpose of this study is to analyse the effects of digitalization on the VAT compliance gap in the European Union countries. The analysis considers the VAT compliance gap as the dependent variable and examines the influence of E-government activities of individuals via websites as an independent variable, as a relevant indicator of digitalization. The research approach methodology consisted in EViews Granger causality tests for the collected data from the EU sources, for a period of ten years (2012-2021). The study results revealed relevant insights and latest information about the connection between e-government users and the VAT compliance gap. This relationship is particularly notable as it emphasizes the potential of digitalization in uplifting tax compliance and improving VAT collection. Studying the impact of digitalization on VAT compliance, the research is intent to provide to the economist, policymakers, and students a deeper understanding of the technology’s impact on tax policies and economic outcome.